Lean TMM application of lean test maturity model framework in an agile environment - Ibañez, Jettrey A.; Rañeses, Nestor (Quezon City University of the Philippines Diliman, 2011)
The Software Delivery (SD) Test Team has been established to provide quality control of web applications developed by the Software Delivery Team to other business groups within Company X. Since the creation of the team, there haven't been standardized processes that were being followed in terms of testing. Normal procedures include reviewing of requirements, creating test cases, testing upon delivery of the software, and providing sign off. Aside from these activities, the roles and responsibilities for each level of testers had not been distinguished, and the current process lacks some supporting activities such as peer review, post mortem and project evaluation that could enhance the quality of testing; thus, increasing the chances of delivering high quality applications. This insufficiency in testing activities led to : delay in delivery of the applications, defects found in production, slow knowledge transfer rate, high failure cost, complaints from business users. Now that the team has grown significantly and is becoming more and more organized, the Lean Test Maturity Model (TMM) project is proposed to align the test processes with industry standards, and at the same time, with the goals of the organization. Lean TMM will map the current test processes with those of the Test Maturity Model Level 3 Framework while maintaining the "lean factor", where activities that are not beneficial or does not fall within the objectives of the organization are removed
The main purpose of this incorporation is to address the first three issues mentioned above causing a domino effect on the last two. Part of this project is to determine the root causes associated with each of the most common issues. By identifying the systemic root causes of the problem, testing activities, tasks and responsibilities from the Test Maturity Model Framework can be adjusted or tailor-fitted to address the problems. The project is expected to (a) define a new Software Delivery Test Engagement Process, (b) develop an initial set of standards for each test activity, and (c) allow members of the SD Test Team to minimize, if not prevent, the most common issues. In order for the project to succeed, all members of the SD Test Team should have a clear understanding of the need to improve the current process. The team was subjected to a series of brownbag sessions on Software Test Management Process focusing on process improvements, TMM in particular. After completion of the brown bag sessions, the team is subjected to the SW TMM Checklist to identify the organization's current TMM level. After completing the checklist, it was agreed that the organization is currently at the TMM Level 3. Around 75 percent of the testers in Company X responded to three questionnaires for the data gathering. The responses gathered provided a clear view of what issues are encountered, which part of the process the issues are encountered, common causes of the issues encountered, and what testing activities should be given priority. A complete why-why analysis based on the responses showed the systemic root causes of the problems. This has been supported by the results of the Failure Mode Effect Analysis. Proposed resolutions are mapped against the TMM Level 3 Activities, Tasks and Responsibilities (ATRs). This allowed for the development of a modified version of the SD Test Engagement Process and initial set of standards per activity. The result of the study is a list of Lean SW-TMM Level 3 ATR; modified to remove those that are not applicable or cannot be applied to the organization's testing process due to company restrictions and redundancy. This list allowed for the development of a new Software Delivery Test Engagement Process. However, the project is only focused on the improvement of a portion of the Software Development Life Cycle; i.e., the testing phase. There are parts of the causes of failure that require changes in other sub-teams of the Software Delivery Team
In partial fulfillment of the requirements in TM 299.
Thesis
Keywords: Organizational effectiveness; Lean test maturity model (TMM) framework